2012
DOI: 10.1245/s10434-012-2386-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Sentinel Node–Positive Breast Cancer Patients after Total Mastectomy without Axillary-Specific Treatment

Abstract: Early-stage breast cancer patients with minimal sentinel node disease experience excellent outcomes without ALND, whether they undergo BCS or TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…18 Smaller studies also including patients treated with both mastectomy and breast conservation with varying radiotherapy approaches have also reported axillary recurrence rates of less than 3% among patients with nodal micrometastases. 1,1922 To our knowledge, our study is the first validation of these favorable results in a large contemporary cohort of patients with T1–T2N0i+/N1mi disease treated with mastectomy and without PMRT.…”
Section: Discussionmentioning
confidence: 55%
“…18 Smaller studies also including patients treated with both mastectomy and breast conservation with varying radiotherapy approaches have also reported axillary recurrence rates of less than 3% among patients with nodal micrometastases. 1,1922 To our knowledge, our study is the first validation of these favorable results in a large contemporary cohort of patients with T1–T2N0i+/N1mi disease treated with mastectomy and without PMRT.…”
Section: Discussionmentioning
confidence: 55%
“…A previously discussed MSKCC paper focused on total mastectomy patients (n = 210) with positive SLNB who did not receive axillary-specific treatment [62,63]. Characteristics and outcomes were compared to similar patients who underwent BCS (n = 325).…”
Section: Involved Sentinel Lymph Nodes and Mastectomymentioning
confidence: 99%
“…Therefore, it is unclear whether ALND is necessary for all node-positive breast cancers. Several retrospective studies where ALND was omitted after detecting micro-or macrometastases in the SLN showed very low rates of axillary recurrence 2729. Two prospective randomized trials confirmed these results for micrometastases and up to two macrometastases.…”
Section: The Role Of Lymph Node Mapping In Cancer Managementmentioning
confidence: 89%